Does acupuncture enhance muscle strength and performance? - Micalos, P. S.; Pak, S. C.; Jesulola, E.; Cannon, J.; Hale, M.; Koo, B.-S. (Strength and Conditioning Journal, 2021)
Acupuncture has gained attention in sports research for enhancing performance and recovery. Although there is substantial recognition for the therapeutic application of acupuncture in a variety of medical conditions, there are limited controlled research trials for acupuncture as a procedure to benefit muscle performance and recovery. Most of the research investigating the mechanism for acupuncture has focused on pain relief. However, there are several physiological effects associated with acupuncture needling, including the therapeutic potential of placebo. Although acupuncture has been shown to have few adverse effects, there is evidence showing a capacity to adversely influence muscle performance.